Mitochondria as Potential Targets in Alzheimer Disease Therapy: An Update - Cenini, Giovanna; Voos, Wolfgang (Frontiers in Pharmacology, 2019)
Alzheimer disease (AD) is a progressive and deleterious neurodegenerative disorder that affects mostly the elderly population. At the moment, no effective treatments are available in the market, making the whole situation a compelling challenge for societies worldwide. Recently, novel mechanisms have been proposed to explain the etiology of this disease leading to the new concept that AD is a multifactor pathology. Among others, the function of mitochondria has been considered as one of the intracellular processes severely compromised in AD since the early stages and likely represents a common feature of many neurodegenerative diseases. Many mitochondrial parameters decline already during the aging, reaching an extensive functional failure concomitant with the onset of neurodegenerative conditions, although the exact timeline of these events is still unclear. Thereby, it is not surprising that mitochondria have been already considered as therapeutic targets in neurodegenerative diseases including AD. Together with an overview of the role of mitochondrial dysfunction, this review examines the pros and cons of the tested therapeutic approaches targeting mitochondria in the context of AD. Since mitochondrial therapies in AD have shown different degrees of progress, it is imperative to perform a detailed analysis of the significance of mitochondrial deterioration in AD and of the significance of a pharmacological treatment at this level. This step would be very important for the field, as an effective drug treatment in AD is still missing and new therapeutic concepts are urgently needed.